2020
DOI: 10.1177/0309324720922085
|View full text |Cite
|
Sign up to set email alerts
|

On the vibration analysis of coupled transverse and shear piezoelectric functionally graded porous beams with higher-order theories

Abstract: This investigation aims to perform a detailed natural frequency analysis of functionally graded porous beams integrated with transverse ( d31) and shear ( d15) piezoelectric layers under short circuit and open circuit electrical conditions. It is assumed that the core layer is made of functionally graded materials containing porosities. Due to the existence of internal pores, the mechanical properties of functionally graded materials are considered according to the modified power-law rule which includes the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Thus, the modified rule of mixture is used here to describe and approximate the effective material properties of the porous FGM substrate. In this regard, two types of porosity distribution, namely Even and Uneven patterns (see Figure 2), are considered; therefore, equation (4) is modified and changed to the following relations for a porous FGM domain (Askari et al, 2021; Wang et al, 2017):…”
Section: Problem Modelingmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the modified rule of mixture is used here to describe and approximate the effective material properties of the porous FGM substrate. In this regard, two types of porosity distribution, namely Even and Uneven patterns (see Figure 2), are considered; therefore, equation (4) is modified and changed to the following relations for a porous FGM domain (Askari et al, 2021; Wang et al, 2017):…”
Section: Problem Modelingmentioning
confidence: 99%
“…They showed that the undesired micro voids can affect the mechanical behavior of FGM structures significantly. Nevertheless, only a few studies have investigated this critical issue and included the effect of porosities in their respective analysis (Askari et al, 2021; Cuong-Le et al, 2021; Moradi-Dastjerdi and Behdinan, 2021; Phung-Van et al, 2019; Thanh et al, 2019). For instance, very recently, Askari et al (2021) developed an analytical work to study the free vibration problem of a simply supported porous FGM beam integrated with thickness-poled and length-poled piezoelectric layers in both SC and OC electrical conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the elasticity theory describes the beam's responses precisely, it is computationally complex and difficult to apply to arbitrary boundary conditions or complicated geometries. As a result, several alternative methods have been proposed, including layer-wise theories, 10,11 equivalent single-layer theories (ESLT), [12][13][14][15] zig-zag theories, [16][17][18][19] and Carrera's Unified Formulation. 20,21 Among these theories, the ESLT is widely utilised due to its formulation simplicity and programming ease.…”
Section: Introductionmentioning
confidence: 99%
“…A functionally graded porous piezoelectric sandwich nanobeam reinforced by graphene platelets was investigated by Chen et al [11] using the Euler-Bernoulli beam theory and a differential quadrature technique in order to capture the effect of flexoelectricity on the vibration responses of the nanobeam. Askari and colleagues [12] used the classical, first-order, and higher-order beam theories to analyze the natural frequencies of FG porous beams combined with transverse and shear piezoelectric layers under electrical conditions of short circuit and open circuit.…”
Section: Introductionmentioning
confidence: 99%